Avoiding Misdiagnosis in Patients with Neurological Emergencies - Jennifer V. Pope; Jonathan A. Edlow (Emergency Medicine International)
Approximately 5% of patients presenting to emergency departments have neurological symptoms. The most common symptoms or diagnoses include headache, dizziness, back pain, weakness, and seizure disorder. Little is known about the actual misdiagnosis of these patients, which can have disastrous consequences for both the patients and the physicians. This paper reviews the existing literature about the misdiagnosis of neurological emergencies and analyzes the reason behind the misdiagnosis by specific presenting complaint. Our goal is to help emergency physicians and other providers reduce diagnostic error, understand how these errors are made, and improve patient care.